Novel Coronavirus (COVID-19) Pandemic: The Role of Printing Media in Asian Countries - Parvin, Gulsan Ara; Ahsan, Reazul; Rahman, Md. Habibur; Abedin, Md. Anwarul (Frontiers in Communication, 2020)
During all critical incidents, the media frame our understanding and create powerful forces at both individual and societal levels. The mental health of readers and viewers can also be affected by the media after tragic events. Potentially, the media have a proactive role in shaping the actions of the mass population and thereby influencing policy actions. The print media especially are considered a key avenue for taking information to the masses. However, in this information and communications technology (ICT) era, people are increasingly reluctant to carry hard-copy newspapers, instead preferring e-newspapers. At the present time, entire newspapers, and especially their opinion sections, are deluged by concerns about the novel coronavirus disease 2019 (COVID-19) pandemic. After China and Japan first encountered COVID-19, other Asian countries began their COVID-19 fight at different times between January and March 2020. All affected countries sought to manage the pandemic in their own way, following lessons learned from China and Japan. Every form of media in affected countries highlighted concerns by presenting news, perceptions, and opinions related to the pandemic. With opinion sections and editorials, the key sections of e-newspapers to reflect experts' perceptions and thoughts, this study aims to examine experts' views in the e-newspapers of five different countries in Asia, in relation to China and Japan. Considering the diversity of socioeconomic and geopolitical settings, five countries—South Korea, Singapore, Iran, India, and Bangladesh—are selected, each represented by one leading English-language e-newspaper. This study explores how experts' perceptions in the studied countries present different aspects of life. It also examines which e-newspaper emphasized which aspect of life and in which period of the outbreak. By intensive text mining in each selected e-newspaper, the study found that experts' opinions addressed diverse issues with regard to COVID-19. These issues are grouped under the following eight categories: health and drugs, preparedness and awareness, social welfare and humanity, the economy, governance and institutions, politics, the environment and wildlife, and innovation and technology. This pioneering study of five different e-newspapers in Asian countries from January to March 2020 presents a similar picture of experts' concerns and their roles in shaping responses to health crises; thus, it plays a role in contributing to policy actions.